Ocean acidification alters anti-predator responses in a competitive dominant intertidal mussel. (February 2022) - Jahnsen-Guzmán, Nicole; Lagos, Nelson A.; Quijón, Pedro A.; Manríquez, Patricio H.; Lardies, Marco A.; Fernández, Carolina; Reyes, Miguel; Zapata, Javier; García-Huidobro, M. Roberto; Labra, Fabio A.; Duarte, Cristian
Abstract: Widespread intertidal mussels are exposed to a variety of natural and anthropogenic stressors. Even so, our understanding of the combined influence of stressors such as predation risk and ocean acidification (OA) on these species remains limited. This study examined the response of the purple mussel ( Perumytilus purpuratus ), a species distributed along Pacific southeastern rocky shores, to the effects of predation risk and OA. Using a laboratory 2 × 2 cross design, purple mussels were either devoid or exposed to predator cues from the muricid snail Acanthina monodon, while simultaneously exposing them to current (500 ppm) or projected OA conditions (1500 ppm). The response of purple mussels to these factors was assessed using growth, calcification, clearance, and metabolic rates, in addition to byssus production. After 60 d, the presence of predator cues reduced mussel growth in width and length, and in the latter case, OA enhanced this response making the effects of predator cues more severe. Calcification rates were driven by the interaction between the two stressors, whereas clearance rates increased only in response to OA, likely explaining some of the growth results. Mussel byssus production also increased with p CO2 but interacted with predation risk: in the absence of predator cues, byssus production increased with OA. These results suggest that projected levels of OA may alter and in some cases prevail over the natural response of purple mussels to predation risk. Considering the role played by this mussel as a dominant competitor and ecosystem engineer in rocky shores, these results have community-wide implications. Graphical abstract: Image 1 Highlights: Combined effects of predation cues (PC) and ocean acidification (OA) were evaluated. Combined effects of PC and OA reduced growth in mussels. Calcification rates were driven by the interaction between PC and OA. Byssus production in mussels increased with OA, in conditions without PC. OA alters the natural response of mussels to predation risk.